Pengaruh Pengendalian Intern Dan Kinerja Karyawan Terhadap Efektivitas Sistem Informasi Akuntansi - Etmunda Felicyta R. Djati; Maria Nona Dince; Emilianus Eo Kutu Goo (Pusat Riset dan Inovasi Nasional, 2022)
This research aims to determine the influence of internal control and employee performance on the effectiveness of accounting information systems. This research uses data obtained from the results of questionnaires distributed to KCU employees. This type of research is quantitative research in associative form, the data sources used are primary and secondary data sources. This research shows that simultaneously internal control variables and employee performance variables jointly influence the effectiveness of the accounting information system. Internal control influences the effectiveness of the accounting information system, and employee performance does not influence the effectiveness of the accounting information system. 39.8 percent of the accounting information system effectiveness variable is explained by the internal control and employee performance variables in this research, the remaining 60.2 percent is explained by other variables that are not in this research.